Distribution Pattern of Active Family Planning Participants by Type of Contraceptive Method in Palopo City, South Sulawesi Province, Indonesia - Astrid Astrid; Merlyn Pattinasarany (Journal of Health Science and Pharmacy, 2025)
Background: The Family Planning (KB) Program is one of the government’s strategic initiatives aimed at controlling population growth and improving the overall quality of life of the community. Despite the availability of various contraceptive methods, their utilization remains uneven across regions, reflecting disparities in access to information, health services, and socio-demographic factors. Objective: This study aims to describe the distribution pattern of active family planning participants according to the type of contraceptive method used across sub-districts in Palopo City, South Sulawesi Province. Method: A quantitative descriptive approach was employed using secondary data obtained from the Central Statistics Agency (BPS) of Palopo City for the year 2019. The data were analyzed descriptively to examine the distribution of contraceptive use across different sub-districts. Results: Data analysis was conducted through graphical interpretation of the distribution of active family planning participants based on contraceptive methods, including intrauterine devices (IUDs), female sterilization (MOW), male sterilization (MOP), condoms, implants, injections, and oral contraceptive pills. The findings indicate that injectable contraceptives were the most commonly used method, particularly in Wara Timur District, followed by oral contraceptives. In contrast, the utilization of long-term and permanent methods, such as IUDs, MOW, and MOP, remained relatively low. Variations in contraceptive use across districts suggest inequalities in access to family planning services and information. Conclusion: The study highlights the need to improve the equitable distribution of family planning services and to strengthen counseling efforts regarding the benefits and potential risks of various contraceptive methods. Such efforts are essential to enable individuals and couples to make informed and appropriate contraceptive choices based on their needs and circumstances.